Phase I trial of myeloablative conditioning with 3‐day total marrow and lymphoid irradiation for leukemia. Issue 2 (2nd November 2022) - Ogawa, Hiroaki; Konishi, Tatsuya; Najima, Yuho; Kito, Satoshi; Hashimoto, Shimpei; Kato, Chika; Sakai, Satoshi; Kanbara, Yasuhiro; Atsuta, Yuya; Konuma, Ryosuke; Wada, Atsushi; Murakami, Daisuke; et al.
Abstract: This prospective phase I trial aimed to determine the recommended dose of 3‐day total marrow and lymphoid irradiation (TMLI) for a myeloablative conditioning regimen by increasing the dose per fraction. The primary end‐point of this single‐institution dose escalation study was the recommended TMLI dose based on the frequency of dose‐limiting toxicity (DLT) ≤100 days posthematopoietic stem cell transplantation (HSCT); a 3 + 3 design was used to evaluate the safety of TMLI. Three dose levels of TMLI (14/16/18 Gy in six fractions over 3 days) were set. The treatment protocol began at 14 Gy. Dose‐limiting toxicities were defined as grade 3 or 4 nonhematological toxicities. Nine patients, with a median age of 42 years (range, 35–48), eight with acute lymphoblastic leukemia and one with chronic myeloblastic leukemia, received TMLI followed by unrelated bone marrow transplant. The median follow‐up period after HSCT was 575 days (range, 253–1037). Three patients were enrolled for each dose level. No patient showed DLT within 100 days of HSCT. The recommended dose of 3‐day TMLI was 18 Gy in six fractions. All patients achieved neutrophil engraftment at a median of 19 days (range, 14–25). One‐year overall and disease‐free survival rates were 83.3% and 57.1%, respectively. Three patients experienced relapse, and no nonrelapse mortality was documented during the observation period. One patient died due to disease relapse 306 days post‐HSCT. The recommended dose of 3‐day TMLI was 18 Gy in six fractions. The efficacy evaluation of this regimen is currently being planned in a phase II study. Abstract : This phase I dose escalation study evaluated the safety of 3‐day total marrow and lymphoid irradiation (TMLI, 14/16/18 Gy in 6 fractions) as myeloablative conditioning for hematopoietic stem cell transplantation. Among enrolled 9 patients (8 with acute lymphoblastic leukemia and 1 with chronic myeloid leukemia), no dose‐limiting toxicity 100‐day after transplant was observed; the one‐year overall survival and non‐relapse mortality were 83.3% and 0%, respectively. The recommended dose of 3‐day TMLI was 18 Gy in 6 fractions, which is currently being planned in a phase II study.